EKSISTENSI ORGANISASI ISLAM DI SULAWESI SELATAN: STUDI GERAKAN SOSIAL POLITIK FRONT PEMBELA ISLAM DI KOTA MAKASSAR - Nurdiassa, Annisa; Kambo, Gustiana Anwar; Muhammad, Muhammad; Zulfikar, Achmad (Jurnal Politik Profetik, 2019)
The Islamic Defenders Front is an Islamic organization that contributes to the democratic process in Indonesia after the New Order government. FPI was declared on August 17, 1998 by adhering to the principle of its movement, namely Amar Ma’ruf Nahi Munkar. This type of research is qualitative research with a case study approach. This study aims to find out how the typology of the movement of Islamic defenders fronts in Makassar, the theory used is the typology theory of social movements proposed by David Aberle, Cameron and Blumer as well as the theory of social movement by Charles Tilly. The results of the research indicate that the organization of Makassar Islamic Defenders Front viewed from the objectives of the movement and the methods used to achieve the objectives, the dimensions of change (who is changed) and the dimensions of change including typology category of social alternative movement category, and social redemptive movement. This movement also potentially transforms into political movements.